Circulation and Exportation of the Japanese Childbirth Model in Southern-East Asia Preliminary Insights from Cambodia - Schantz, Clémence; Petitet, Pascale Hancart (Rethinking Asia in World Politics, 2023)
Globally, maternal health matters and birthing ideologies and practices still generate much controversy. On the one hand, those who are promoting the medicalization of childbirth argue that the mortality and morbidity risks justify the imposition of biotechnological standards and practices. On the other hand, activists for demedicalization of birth are denouncing gynecological and obstetric violence, and pointing the pathologies induced by overuse of technologies. These movements, which are part of the current’s feminist calls, advocate a women’s reappropriation over their own bodies. The paper, based on long term and more recent ethnographical investigations aims to explore these political, cultural and social controversies by examining the recent initiatives in reproductive health domain carried by Japanese cooperation in South-East Asia. Since the 2000s, JICA (Japanese agency for international cooperation), as part of its infrastructure development, institutional strengthening and training programs, has indeed carried out numerous initiatives. One aims at improving the quality of maternal health care with two main objectives: the reduction of cesarean section rates and the humanization of birth.